Deteksi Objek Terapung pada Sungai Martapura dengan Metode Haar Like Feature Menggunakan Kamera Smart Phone - Saubari, Nahdi; Ansari, Rudy; Gazali, Mukhaimy (Universitas Diponegoro, 2019)
Martapura river is the center of Banjarmasin’s local life, especially for water transportation and its famous floating market tourism spot. Due to various floating objects in Martapura river, a method to detect those objects is needed to control the condition of the river. In general, there are several methods to detect objects such as Gaussian, Support Vector Machine (SVM), Independent Component Analysis (ICA) and the newest method called Haar Like Feature (HLF). Those first three methods often used to detect moving object, while HLF mostly used to detect human’s face. This research aimed to examine the use of HLF method to detect floating objects in Martapura river by using smartphone’s camera with the specification of 16Megapixel and 1080p resolution. The data collected with random sampling technique in two different spots in Banjarmasin at different times. Images and videos then examined using HLF method. The result shows that HLF method by using smartphone camera cannot be used to identify any floating objec